‘MASUK NAPI KELUAR SANTRI’: PEMBINAAN NARAPIDANA BERBASIS PESANTREN DI LAPAS KELAS II A KOTA LUBUKLINGGAU - Savitri Restu Wardhini; Rama Wijaya K.W; Pasiska Pasiska (Psychosophia: Journal of Psychology, Religion, and Humanity, 2020)
This research will examine the psychology of communication in the community fostered at the Class II A Lubuklinggau penitentiary facility, the research method used is qualitative research with a case study approach, then in data collection by interviewing, documentation and in data processing used with data reduction, then the presentation of the data and in the end the data is concluded. The communication psychology of clerics and prisoners in the class II A penitentiary boarding school in Lubuklinggau City is very influential. Because some prisoners have shown a positive response while receiving guidance at this pesantren. Based on the results of observations, interviews, and documentation, the researchers got the results that the implementation of strategic management in the Class II A penitentiary of Lubuklinggau City ran optimally, it can be proven that the number of prisoners after leaving the coaching process can live and survive and are able to be accepted in the community, although not yet within the scope broad.